Evaluation and management of thyroid incidentalomas detected prior to the parathyroid surgery. (September 2018) - Vaiman, Michael; Halevy, Ariel; Cohenpour, Mehrzad; Peer, Michael; Bekerman, Inessa; Gavriel, Haim
Abstract: Background: We investigated the management of thyroid incidentalomas associated with cases of parathyroid lesions in order to suggest a practical approach to their management from a surgical point of view. Methods: 639 patients underwent radiological and ultrasound investigation of the thyroid area because of parathyroid disorders and parathyroidectomy and had at least three years of follow-up. All follow-up data for these cases were investigated from the moment the lesion was detected and up to the last report. Results: Out of 639 cases, incidental or asymptomatic thyroid nodules were found in 179 patients (28%), of which, 22 patients were operated (parathyroidectomy + thyroidectomy) and 157 remained with the nodules. For these patients, the average period of follow-up was 7 years 5 mo. Following the results of the follow-up, 52 patients (33%) were suggested to have surgery of the thyroid gland and 49 were operated (16 total thyroidectomies and 33 hemithyroidectomies). The complications after the second surgery included recurrent laryngeal nerve palsy (n = 3), superior laryngeal nerve palsy (n = 1), permanent hypocalcaemia (n = 8), and surgical damage to the internal jugular vein (n = 1). All complications occurred at the previously operated side of the neck. Conclusion: While surgery remains the management of choice for malignant thyroid incidentalomas, for benign cases, if an asymptomatic thyroid nodule was detected inside the thyroid lobe on the side of planned parathyroidectomy and if the size of the nodule is ˃1.5 cm we suggest combined parathyroidectomy + hemithyroidectomy. Highlights: 639 patients underwent radiological and ultrasound investigation of the thyroid area because of parathyroid disorders. Incidental or asymptomatic thyroid nodules were found in 179 patients (28%). Malignant thyroid incidentalomas are to be operated simultaneously with parathyroidectomy. Benign unilateral incidentalomas are to be operated simultaneously with parathyroidectomy. Benign contralateral incidentalomas are to be observed.